100 questions & answers about schizophrenia : painful minds - DeLisi, Lynn E. (Jones and Bartlett Publishers, 2011)
Overview: Schizophrenia is a chronic, severe mental illness that can be devastating for patients and their loved ones. Whether you are a newly diagnosed patient or a relative of someone suffering from this condition, this book offers help. 100 Questions & Answers About Schizophrenia: Painful Minds, Second Edition, provides authoritative, practical answers to your questions about symptoms, diagnosis, treatment options, sources of support, and much more. Expert psychiatrist Dr. Lynn E. DeLisi has updated her book with new facts, statistics, and helpful information that many patients and their families seek. This book is an invaluable resource for anyone coping with the physical, mental, and emotional turmoil of schizophrenia
Keywords: Schizophrenia -- Miscellanea; Schizophrenia -- Popular works